Study on the Mechanical Properties of Coal Weakenedby Acidic and Alkaline Solutions - Dong Xu; Mingshi Gao; Yichao Zhao; Yongliang He; Xin Yu (Advances in Civil Engineering)
A novel method for fracturing coal is presented in this paper. A chemical solution is injected into coal under high pressure, whereby the coal is fractured and subsequently weakened by chemical erosion over time to produce an anti-impact soft structure. In this study, the mechanical properties of coal under chemical erosion were investigated, and the fracturing design parameters were optimized. The uniaxial compression test and the split Hopkinson pressure bar (SHPB) test were used to determine the dynamic and static mechanical properties of coal after 20 days of immersion in different chemical solutions. After chemical solution erosion, the dynamic and static compressive strengths and elastic modulus of the coal decreased according to an exponential power law in the damage variable. The chemical treatment increased the duration of the pore compaction stage and decreased that of the elastic deformation stage, while decreasing the brittleness and increasing the ductility of coal. The acoustic emission (AE) curve of the immersed coal samples consisted of four stages corresponding to those of the stress-strain curve: pore compaction-closure, a slowly rising linear elastic regime, steady-state prepeak crack propagation, and unsteady crack propagation at the peak strain. The increase in the damage variable of the coal sample from chemical erosion led to a lower dissipated energy, a higher fractal dimension, and a more fragmented coal sample. The effect of the investigated chemical solutions on weakening the coal mechanical properties decreased in the following order: alkaline solution > acidic solution > NaCl solution > distilled water. The experimental results provide a reference for weakening fractured coal seams.